2000
DOI: 10.1046/j.1432-1327.2000.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the phosphatase activity of calcineurin by oxidants and antioxidants in vitro

Abstract: Previous research has indicated that oxidants, antioxidants and the intracellular redox state regulate the activities of a variety of protein tyrosine kinases, protein tyrosine phosphatases, phospholipases and transcription factors. In order to explore the redox regulation of the serine/threonine phosphatase calcineurin, we have investigated the effects of a variety of oxidants and antioxidants on calcineurin phosphatase activity in vitro. The oxidants hydrogen peroxide, superoxide and glutathione disulfide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 65 publications
4
49
0
2
Order By: Relevance
“…It has been shown that calcineurin is sensitive to oxidative stress and may be modulated by the intracellular redox potential (48). In general, thiol antioxidants, such as NAC, GSH, and cysteine, appear to activate calcineurin, while oxidants, such as hydrogen peroxide, inactivate this phosphatase (49). These studies together with our data suggest an enhanced activation of NFATc2 in NAC-pretreated cells, which may explain in part the enhanced expression of IL-4.…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that calcineurin is sensitive to oxidative stress and may be modulated by the intracellular redox potential (48). In general, thiol antioxidants, such as NAC, GSH, and cysteine, appear to activate calcineurin, while oxidants, such as hydrogen peroxide, inactivate this phosphatase (49). These studies together with our data suggest an enhanced activation of NFATc2 in NAC-pretreated cells, which may explain in part the enhanced expression of IL-4.…”
Section: Discussionsupporting
confidence: 75%
“…Our results are in agreement with those reported by Sommer et al (2000), who found that PDTC increased the activity of purified CN but inhibited most of the CN activity present in fibroblast lysates likely by chelating an exogenous metal(s) needed for its activity. By metal abstraction, PDTC inactivates copper/zinc superoxide dismutase (Kelner et al 1989), a stabilizing factor in intact cells, which protects CN from inactivation (Wang et al 1996).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the intracellular levels of GSH seem to be critical for Ang II-promoted induction of CN expression and activity. Other authors have described similar increases in CN activity in fibroblasts on incubation with two other thiol-reducing agents, N-acetylcysteine and lipoic acid (Sommer et al 2000). The reversibility of CN inhibition by GSH is especially important in the emerging field of redox signaling.…”
Section: Discussionmentioning
confidence: 72%
“…Antioxidant activity is the most obvious potential mechanism, particularly since immune responses proceed more efficiently in reducing environments (6,40). Additional possibilities for mechanistic roles of ascorbic acid in promoting the immune response include modulation of phosphatase activity (31,41), post-translational activation of AP-1 transcription factors (1), and epigenetic regulation of gene expression (8). A number of the biological activities of ascorbic acid trace to its role as a cofactor required for optimal activity of ferrous iron-and 2-oxoglutarate (Fe 2 + and 2-OG)-dependent dioxygenases, which have been implicated in regulating a wide range of processes, including gene regulation, nucleotide metabolism, and oxidative repair of DNA (30).…”
Section: Innovationmentioning
confidence: 99%